Tricks of the Medieval Trades. The Trinity Encyclopedia: A Collection of Fourteenth-Century English Craft Recipes - Bruquetas Galán, Rocío (Ge-conservacion, 2019)
Tricks of the Medieval Trades. The Trinity Encyclopedia: A Collection of Fourteenth-Century English Craft Recipes Autor/es: Mark Clarke Editor: Archetype Publications Ltd. (31 de diciembre de 2018) ISBN-10: 1909492655 ISBN-13: 978-1909492653 Dimensiones: 210 x 297mm Páginas: 132 Idioma: Inglés